SYSTEM DYNAMIC ANALYSIS OF RESOURCES MANAGEMENT IN LAYUR FISHERIES IN UJUNG GENTENG, SUKABUMI - Ahmad, Kiffah Kayyisah; Rosalia, Ayang Armelita; Lestari, Della Ayu (JURNAL LEMURU, 2023)
Ujung Genteng is one of the areas in Sukabumi which has a large capture fisheries sector. Various capture fishery commodities, especially layur fish which are classified as demersal species, are superior commodities. The layur commodity is caught using hand line and bottom longline by Ujung Genteng fishermen. However, capture fisheries production, especially in 2020 and 2022, has decreased. System dynamic analysis on the management of layur fisheries resources is divided into three sub-model groups: the ecological, social, and economic sub-models. In obtaining results on a dynamic system, accurate data is needed on all stakeholders related to the management of layur fisheries resources, namely the community, fishermen, village government, managers of Fish Auction Places (TPI), and related Fisheries Service data. However, limited data sources in the Ujung Genteng area have made accurate data on the striped fishery only started in 2019. The dynamic analysis results explain in detail the factors causing the decline in catches in the past two years and display the estimated values for each variable that will experience an increase except for Layur catch production.